CURRENT STATUS AND SOME FACTORS RELATED TO SOIL-TRANSMITTED HELMINTH INFECTION IN PEOPLE AGED 2 - 65 YEARS OLD IN BINH LIEU DISTRICT AND QUANG YEN TOWN, QUANG NINH PROVINCE IN 2023 (Vietnam Journal of Community Medicine, 2026)
The research results of the project showed that the overall rate of worm infection was 11.9%, of which whipworm was the highest at 6.25%, followed by roundworm at 3.75%, and hookworm was the lowest. mine 1.9%. The rate of worm infection is mainly in people aged > 15 years old, no cases of worm infection were detected in those aged < 15 years. The rate of worm infection in women is higher than in men in both research locations, Quang Yen Town and Binh Lieu District. People who do not use labor protection and regularly drink plain water have a higher rate of worm infection than people who use labor protection and do not drink plain water, and people who do not wash their hands regularly before eating and after defecation. had a higher rate of worm infection (60.4% compared to 1.2%), people who used hygienic toilets had a lower rate of worm infection than people who did not use hygienic toilets (2.1 % compared to 68.6%), people who regularly take deworming medication have a lower rate of worm infection than people who do not take deworming medication regularly (0.6% compared to 65%). It is necessary to develop a deworming intervention plan for people throughout the province, and at the same time communicate and advise people on knowledge about soil-transmitted helminth diseases.
Keywords: Worm infection rate, infection intensity, influencing factors; Worms are transmitted through soil.